2020
DOI: 10.1590/1678-6971/eramd200122
|View full text |Cite
|
Sign up to set email alerts
|

Personal Organizational Well-Being and Quality of Organizational Life: The Mediating Role of Organizational Culture

Abstract: Purpose: To test models of mediation and moderation of the organizational culture, competing values and styles of organizational operation having quality of organizational life (QOL) as antecedent and personal organizational well-being (POW) as consequent. Originality/value: Literature has presented tests of mediation/moderation models to understand well-being of employees and support leadership in the implementation of strategies that fit into the organizational realities. Organizational culture has been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
2
Order By: Relevance
“…In this context, culture refers to how groups, including companies, interact internally and externally. As a result, the cultural coherence of a specific organization is determined by the sufficiency of the group’s artistic mission, strategies, and processes 37 . These cultural techniques are referred to as “macro dimensions,” which are characterized by the dynamic nature of organizations, in which numerous forces interact and impact one another and are thus sensitive to changes that may alter the structure of the organization 37 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, culture refers to how groups, including companies, interact internally and externally. As a result, the cultural coherence of a specific organization is determined by the sufficiency of the group’s artistic mission, strategies, and processes 37 . These cultural techniques are referred to as “macro dimensions,” which are characterized by the dynamic nature of organizations, in which numerous forces interact and impact one another and are thus sensitive to changes that may alter the structure of the organization 37 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, this study is interdisciplinary in nature as it relates to the fields of higher education and quality management; therefore, it has implications for administrative managers and quality managers in both fields due to its relevance and interesting insights. Second, while several studies have investigated the mediating role of organizational culture (Abdullah et al, 2015; TQM 36,2 Paz et al, 2020;Yajid and KKhatibi, 2020), however, there is little evidence that researchers have investigated quality culture as a mediator related to accreditation and higher education performance in university contexts around the world. Finally, the findings of this study are important for both global and local universities, as there is growing interest in understanding how accreditation and a culture of quality can improve the academic quality, performance, credibility and public image of universities around the world.…”
Section: Study Implications and Limitationsmentioning
confidence: 99%
“…First, this study is interdisciplinary in nature as it relates to the fields of higher education and quality management; therefore, it has implications for administrative managers and quality managers in both fields due to its relevance and interesting insights. Second, while several studies have investigated the mediating role of organizational culture (Abdullah et al ., 2015; Paz et al. , 2020; Yajid and KKhatibi, 2020), however, there is little evidence that researchers have investigated quality culture as a mediator related to accreditation and higher education performance in university contexts around the world.…”
Section: Study Implications and Limitationsmentioning
confidence: 99%
“…An organisation has a different status, age, gender, nationality of workers, whose approach to the organisation's values may differ. Research has shown that such individual features as personality traits, gender, race and age have a significant effect on some organisational values, and these groups differ significantly in their perception of the importance of certain organisational values (Martins & Coetzee, 2011, Paz et al, 2020; therefore, it is necessary to explore and understand the assumptions and reasons of the value perception and acceptance of differences and similarities.…”
Section: Literature Reviewmentioning
confidence: 99%